Wpływ parametru luki na ryzyko opcji sprzedaży - Dziawgo, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
Gap options are singular payoffs options characterized by discontinuity of pay-offfunction. The article presents the properties of the gap put option: construction ofinstrument, the pay-off function, the pricing model, the influence of selected factorson the pricing and the value measurements of risk (coefficients delta, gamma,vega, theta, rho). The paper analyses the influence of the underlying instrument’sprice, the time maturity and the gap parameter on the risk performance of the putoptions using pricing simulations of the currency options on EUR/PLN.